Intercultural Marketing : Theory and Practice - Beveridge, Ivana, author 636157 (New York, NY : Routledge, 2021)
"With companies actively marketing products and services beyond their borders, marketers must understand culturally ingrained consumer behavior throughout the world. Focusing on psychological and social dimensions of these behaviors, this textbook brings together academic research and contemporary case studies from the marketing practice. Built on a strong, cross-disciplinary theoretical foundation, this concisely written text is a practical guide to understanding the intricacies of cultural influence on consumption, and for the design and implementation of effective intercultural marketing strategies, focused on branding and promotion. The book uses representative, well-known corporate cases while also including dynamic examples from the sharing economy, blockchain, and emerging economy companies in international markets. Incorporating strategy, sociology, linguistics, cross-cultural communications, psychology, philosophy, religious studies, and economics, the book is particularly distinguished from the mainstream by introducing non-Western frameworks. Upper-level undergraduate and postgraduate students of marketing and international business will benefit from the book's new concepts and novel methods, as well as clear objectives, examples, and discussion topics in each chapter. Instructors will appreciate the inclusion of a semester-long project for students, allowing them to wear the 'practitioner's hat' and including practice in a netnographic research method"--